2010
DOI: 10.1177/0095244310362733
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Natural Rubber Filled with Ultra Fine Acrylate Rubber Powder

Abstract: Properties of natural rubber (NR) filled with various loadings of ultra-fine vulcanized acrylate rubber powder (ACMP) were investigated. ACMP loading was varied from 0 to 20 phr and, after compounding, the compound properties were determined. Results reveal that increasing ACMP loading leads to improved processability, as evidenced by the reduction of both mixing energy and Mooney viscosity. ACMP, however, has negative effect on cure, that is, both scorch time and optimum cure time are prolonged while the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Despite the extremely low swelling degree, modulus of the rubber vulcanisates tends to increase slightly (10-20%) whereas the elongation at break is slightly decreased (<18%) after oil immersion which could be attributed to the more tightened rubber network in the swollen specimens. Similar findings have previously been reported [19,20]. Taking as a whole, the densely crosslinked and heavily filled NBR vulcanisates possess an excellent oil resistance and, thus, the effects of resin type and content on oil resistance of the NBR vulcanisates are not obvious (the variations found herein are within the experimental error limits), even though the addition of crosslinked phenolic resin into the rubber network should theoretically increase oil resistance of the rubber vulcanisates due to the existence of additional resin network which can resist the oil swelling.…”
Section: Resultssupporting
confidence: 93%
“…Despite the extremely low swelling degree, modulus of the rubber vulcanisates tends to increase slightly (10-20%) whereas the elongation at break is slightly decreased (<18%) after oil immersion which could be attributed to the more tightened rubber network in the swollen specimens. Similar findings have previously been reported [19,20]. Taking as a whole, the densely crosslinked and heavily filled NBR vulcanisates possess an excellent oil resistance and, thus, the effects of resin type and content on oil resistance of the NBR vulcanisates are not obvious (the variations found herein are within the experimental error limits), even though the addition of crosslinked phenolic resin into the rubber network should theoretically increase oil resistance of the rubber vulcanisates due to the existence of additional resin network which can resist the oil swelling.…”
Section: Resultssupporting
confidence: 93%
“…The main factors of mechanical energy dissipation of the tip and consequent phase change are the viscoelastic, adhesive and topographical properties of the region being examined. In addition, it allows to obtain new information about the polymers surface such as tribological data [3] , local contaminants [6] , morphology [17, , distribution of phases in blends and composites [41][42][43][44][45][46][47] , compatibility between the phases of polymer blends and interaction between nanocomposites phases [48][49][50][51][52][53][54] , polymeric chains conformation [7,38] , cross-link density [55][56][57] , dispersion of fillers in the polymeric matrix [10,12,16,48,49,[58][59][60][61][62][63][64][65][66][67][68][69] , among other applications.…”
Section: De Sousa F D B; Scuracchio C H -The Use Of Atomic Formentioning
confidence: 99%
“…AFM study gives a higher particle thickness which may be due to the tip broadening effect. In a similar work, Sae-Oui et al [58] prepared nanocomposites NR/acrylate rubber powder (ACMP) in an internal mixer, and studied the dispersion of the filler in the rubber matrix by AFM. A high level of ACMP dispersion was achieved in concentrations until 5 phr.…”
Section: De Sousa F D B; Scuracchio C H -The Use Of Atomic Formentioning
confidence: 99%
“…It was found that the M H value of TMTD-based NR/(R-EPDM) was higher than those of CBS, TBBS, and MBT, respectively, which indicated that the TMTD-based NR/(R-EPDM) might have affected the stiffness or hardness of the blends rather than those CBS-, TBBS-, and MBT-accelerated NR/(R-EPDM) blends. High stiffness could lead to a higher restriction to molecular motion of the macromolecule or tended to impose extra resistance to flow and led to high stiffness [28,29].…”
Section: Cure Characteristicsmentioning
confidence: 99%